PENGARUH EXPERIENTIAL MARKETING DAN PERSEPSI NILAI TERHADAP PEMBELIAN ULANG MELALUI KEPUASAN (Studi Pada Penumpang Kereta Api Argo Bromo Angkrek) - Vanny Fajryanti; Naili Farida (Universitas Diponegoro, 2018)
The problem faced by the Argo Bromo Anggrek train is the decline in the number of passengers of the Argo Bromo Anggrek train that occurs for three years continuously so that it affects the achievement of the target. The perceived factors that can influence consumer interest to buy again include experiential marketing and value perception.This research was conducted to explain the effect of experiental marketing and perception of value to the emergence of satisfaction. In this research use purposive random sampling sampling technique so that can be taken 100 passenger of Argo Bromo Anggrek Executive Train. The data analysis used is regression.The results showed that experiental marketing has a positive and significant influence on the interest of repurchasing (Y), the perception of value (X2) has a positive and significant effect on customer satisfaction (Y1). The results also show that there is a positive and significant influence between experiential marketing and value perception jointly to customer satisfaction. Customer satisfaction has a positive and significant influence on the interest of repurchasing.